CRITICAL DISCOURSE ANALYSIS OF SAMPOERNA MILD CIGARETTE ADVERTISING ‘TANYA KENAPA’ EDITIONS - Andri Wicaksono (State Institute for Islamic Studies IAIN of Metro, 2015)
Cigarette advertising A-Mild brand brings an intelligent and critical condition of society. A mild ad-was unique and entertaining. This study aimed to describe forms of diction and meaning a reference in A Mild cigarette advertising discourse of ‘Tanya Kenapa' edition. The approach used in this research is descriptive qualitative. The object of this research is a fragment of A Mild cigarette advertising discourse of 'Tanya Kenapa’ edition.The results showed that the meaning of the image and text advertisement serving A-Mild do not have ideological ties, stable and secure, even ironical. The effects of humor or absurdity resulting from distortion or play on an existing expression. Sampoerna A Mild invites customers to not hesitate be critical of the various phenomena that occur in the community. In the ads, Sampoerna A Mild cigarettes tend to avoid adverse effects for consumers so the fact that cigarettes are harmful to the health of consumers covered with critical image of attached to the text and context of advertising discourse.